Effects of Red Light Night Break Treatment on Growth and Flowering of Tomato Plants - Cao, Kai; Cui, Lirong; Ye, Lin; Zhou, Xiaoting; Bao, Encai; Zhao, Hailiang; Zou, Zhirong (Frontiers in Plant Science, 2016)
Compact and healthy young plants increase crop production and improve vegetable quality. Adverse climatic conditions and shading can cause young plants to become elongated and spindly. We investigated the effects of night break (NB) treatments on tomato plants using red light (RL) with an intensity of 20 µmol•m2•s-1. Tomato plants were subjected to NB treatments with different frequencies ranging from every 1, 2, 3, and 4 h, and plant growth, flowering, and yield were monitored. The results showed that with the increase of RL NB frequency, plant height decreased, stem diameter increased, and flower initiation delayed, the content of indole-3-acetic acid (IAA) and gibberellin 3 (GA3) in the leaf and stem declined. When the RL NB frequency was every 1 h, the heights of tomato plant decreased by 32.73% compared with the control, the diameter of tomato plants increased by 27.09% compared with the control, the number of leaves produced before flowering increased to 11, compared with 8 in the control, the contents of IAA and GA3 in the leaf decreased by 33.3% and 41.29% respectively compared with the control, the contents of IAA and GA3 in the stem decreased by 56.04% and 57.14% respectively compared with the control. After RL NB treatments, tomato plants were transplanted into a solar greenhouse to evaluate tomato yield. When tomato plants pre-treated with RL NB, per tomato fresh weight of the first spica increased with the increase of RL NB frequencies. These results indicate that more compact and healthier tomato plants could be gotten by RL NB treatments and improve tomato early yield.